1967
DOI: 10.1128/jb.94.4.812-814.1967
|View full text |Cite|
|
Sign up to set email alerts
|

In Vitro Acetylcholinesterase Inhibition by Type A Botulinum Toxin

Abstract: Type A botulinum toxin was studied for its ability to inhibit the action of acetylcholinesterase. The chromogenic substrate, indophenyl acetate, was used for assay ofenzyme activity. Inhibition ofenzyme function was detected through use ofboth 6.6 X 10-6 mg (20 LDS0) and 6.6 x I010 mg (2 x 10-3 LD50) of type A botulinal toxin. Control assays were performed by use of both homologous antitoxin and heterologous antitoxins (types B and E). Enzyme inhibition was effectively prevented by use ofhomologous antitoxin o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1971
1971
2000
2000

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…(Cook, 1955a(Cook, , 1955b. The fact that inhibition of acetyl cholinesterase occurs _in vitro through the action of type A botulinum toxin was reported earlier by Marshall and Quinn (1967). The spectrophotometric methods and equipment used by these workers were also used in these studies.…”
Section: Literature Reviewmentioning
confidence: 85%
See 4 more Smart Citations
“…(Cook, 1955a(Cook, , 1955b. The fact that inhibition of acetyl cholinesterase occurs _in vitro through the action of type A botulinum toxin was reported earlier by Marshall and Quinn (1967). The spectrophotometric methods and equipment used by these workers were also used in these studies.…”
Section: Literature Reviewmentioning
confidence: 85%
“…Johnson et al (1965) studied serological procedures which might be applicable to the detection of botulinal toxins in foods. However, this method is rather cumbersome and has proved to be of little practical importance, Recently, Marshall and Quinn (1967) showed that type A toxin is capable of inhibiting the enzyme acetylcholinesterase _in vitro, and also that the inhibition is detectable spectrophotometrically. Reports con cerning the vitro estimation of organic phosphate inhibitors of acetylcholinesterase are many and since type A toxin does inhibit acetyl cholinesterase, spot tests based on the methods of Cook (1955aCook ( , 1955b and Sandi and Wight (1961), for example, may be used to show enzyme in hibition qualitatively.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations